Requirements for a patient recruitment system - Schreiweis, Björn; Bergh, Björn (Digital healthcare empowering Europeans, 2015)
Computerization and increasing need for evidence based medicine are not stopping at biomedical research. Clinical trials need participants and the problem of matching patients with eligibility criteria to support clinical trials has many different solutions. A detailed analysis of stakeholders' requirements would help implementing better patient recruitment systems (PRSs) in the future. Thus we decided to analyse the requirements in literature and talk to stakeholders what they feel the features of PRSs should be. Including patients and data privacy officers as stakeholders gives a holistic overview. Requirements are overlapping between different stakeholders with each stakeholder adding a different view on PRSs. Requirements implemented in current PRSs overlap mostly with requirements expressed by physicians and researchers. Especially patients' requirements (e.g. not having to enter medical data themselves) on PRSs give the impression that PRSs need to integrate with EHR systems or even PEHRs.